Polyethylenimine-based micro/nanoparticles as vaccine adjuvants [Corrigendum] - Shen C (Dove Medical Press, 2017)
Shen C, Li J, Zhang Y, et al. Int J Nano. 2017;12:5443–5460.The affiliations were presented as:Chen Shen1Jun Li1Yi Zhang1Yuce Li2Guanxin Shen3Jintao Zhu2Juan Tao11Department of Dermatology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, China; 2School of Chemistry and Chemical Engineering, Huazhong University of Science and Technology, Wuhan, China; 3Department of Immunology, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, ChinaThe affiliations should have contained the postcodes and are corrected here:Chen Shen1Jun Li1Yi Zhang1Yuce Li2Guanxin Shen3Jintao Zhu2Juan Tao11Department of Dermatology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430022, China; 2School of Chemistry and Chemical Engineering, Huazhong University of Science and Technology, Wuhan 430074, China; 3Department of Immunology, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430022, ChinaRead the original article